2018
DOI: 10.1177/1350508418805285
|View full text |Cite
|
Sign up to set email alerts
|

Theorizing affective ethnography for organization studies

Abstract: This article introduces a new label, ‘Affective Ethnography’, and grounds it within the debates on post-qualitative methodologies and affective methodologies. Affective ethnography is theorized as a style of research practice that acknowledges that all elements—texts, actors, materialities, language, agencies—are already entangled in complex ways, and that they should be read in their intra-actions, through one another, as data in motion/data that move. I discuss three pillars for affective ethnographies that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
185
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(193 citation statements)
references
References 111 publications
(92 reference statements)
1
185
0
7
Order By: Relevance
“…This story from the fieldwork gives an idea of the kind of problems that a researcher or a group of researchers face in trying to understand and use their embodied experience in the interpretation and representation of research data. It was an intense experience and it was the inspiration for theorizing affective ethnography sometime later (Gherardi, 2018). In recognizing the centrality of the bodies, the pervasiveness of carnal know-how, and the affective resonance with the persons, the materialities, and the emplacements of the fieldwork situation, affective ethnography is centered on three aspects related to bodily presence in doing fieldwork and the bodies' capacity to affect/be affected.…”
Section: Q3 Identifying Affective Traces Of Embodied Processes In Emmentioning
confidence: 99%
See 1 more Smart Citation
“…This story from the fieldwork gives an idea of the kind of problems that a researcher or a group of researchers face in trying to understand and use their embodied experience in the interpretation and representation of research data. It was an intense experience and it was the inspiration for theorizing affective ethnography sometime later (Gherardi, 2018). In recognizing the centrality of the bodies, the pervasiveness of carnal know-how, and the affective resonance with the persons, the materialities, and the emplacements of the fieldwork situation, affective ethnography is centered on three aspects related to bodily presence in doing fieldwork and the bodies' capacity to affect/be affected.…”
Section: Q3 Identifying Affective Traces Of Embodied Processes In Emmentioning
confidence: 99%
“…To interpret data is not limited to personal/cognitive skills; it also is to be bodily able to engage in affective manner in the research practices. Instead of a traditional perspective focused on a method that drives the researcher through technical set of procedures to be employed in the "right" way, the embodied practice-based research is a "style" of doing research wherein the researcher is able to recognize or identify something when he/she see or read it (Gherardi, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Beyes & Steyaert, 2012;Ropo et al, 2015;Thanem, 2012), and also to the emerging literature on affect in organizations (e.g. Fotaki et al, 2017;Gherardi, 2017Gherardi, , 2018Pullen et al, 2017;Thanem & Wallenberg, 2015). The findings of the study are reported in four essays.…”
Section: Aim Of Studymentioning
confidence: 78%
“…Finally, Essay 4 addresses the research aim by showing how affective ethnography (Gherardi, 2018;Stewart, 2007) as a research approach can help scholars in developing sensitivity towards the affective quality of space. This paper suggests that examining and writing about this quality entails moving beyond representational epistemology, which underpins much of the existing ethnographic studies of space in organizational literature.…”
Section: Aim Of Studymentioning
confidence: 99%
“…To mention a few examples in management and organization studies more specifically, I am thinking, for example, of Barbara Czarniawska's seminal work on narratives and shadowing (Czarniawska, , ), of John Law's messy methods (Law, ) and of Van Maanen's classic tales of the field (Van Maanen, ). Along the lines of these transformative works, and taking stock on their own work and that of others on embodiment in social sciences (e.g., Gherardi, ; Pullen & Rhodes, ; Thanem & Wallenberg, ), Thanem and Knights argue that every research step is embodied — even analysis and writing. This allows us not only to feel less ashamed of our bodily presence in the field, but also to feel fully entitled to use and acknowledge our bodies in research.…”
mentioning
confidence: 99%